Monitoring The Implementation Of Internal Audit Recommendations: A Three-Stage Control Indicator (Action-Progress-Impact) - Saitmuratov Saitmurat (Open Academia, 2025)
This paper proposes a three-stage control indicator model—Action, Progress, and Impact (API)—to enhance the monitoring and implementation of internal audit recommendations. By structuring the process into these three stages, the API framework aims to ensure not only the prompt execution of audit findings but also the continuous tracking of progress and evaluation of long-term impacts. Drawing on insights from public sector organizations in Romania and state-owned enterprises in Indonesia, the paper demonstrates how the API model can promote transparency, accountability, and sustained performance improvements. Despite challenges such as data system integration and cultural resistance, the API framework offers a systematic and holistic approach that aligns internal audit practices with organizational governance and strategic objectives. The findings underscore the potential of the API model to strengthen internal control, risk management, and overall organizational resilience.
Keywords: Internal audit; Action-Progress-Impact; framework